2015
DOI: 10.1371/journal.pone.0145327
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethanol on the Morphological and Biochemical Properties of Individual Human Red Blood Cells

Abstract: Here, we report the results of a study on the effects of ethanol exposure on human red blood cells (RBCs) using quantitative phase imaging techniques at the level of individual cells. Three-dimensional refractive index tomograms and dynamic membrane fluctuations of RBCs were measured using common-path diffraction optical tomography, from which morphological (volume, surface area, and sphericity); biochemical (hemoglobin (Hb) concentration and Hb content); and biomechanical (membrane fluctuation) parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 61 publications
1
42
0
1
Order By: Relevance
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 95%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%
“…RBC is one of most popular candidates due to its special biconcave shape and simple inner structures [100104] [Fig. 7(a)].…”
Section: Applicationsmentioning
confidence: 99%
“…To quantify Hb, mean corpuscular Hb concentration (MCHC) and mean corpuscular Hb content (MCH) are being used for medical diagnosis on a daily basis in medical laboratories [120]. MCHC and MCH values can be measured with TPM, which can be used to quantitatively investigate the responses of RBCs to exogenous stimuli or their endogenous functional disorders [52,54,102104]. By comparing the MCHC and MCH values of RBCs from healthy humans and patients with iron deficiency anemia (IDA), high reticulocyte content, and hereditary spherocytosis, Kim et al [120] found that the IDA RBCs have significantly decreased MCH values, whereas reticulocytes have relatively larger MCH values, which is consistent with the fact that the oxygen carrying capacity of RBCs is primarily determined by the amount of Hb.…”
Section: Applicationsmentioning
confidence: 99%
“…[4][5][6] The label-free and noninvasive character makes it attractive in biomedical imaging, especially for cultured cells. 7,8 However, most of the current methods require around 50 quantitative phase images acquired at different angles [9][10][11] or different depths 6 for optical tomography. This speed limitation greatly restricts its field of applications.…”
Section: Introductionmentioning
confidence: 99%